Segmentation Analysis using Synthetic Speech Signals - Greibus, M.; Telksnys, L. (Elektronika ir Elektrotechnika, 2012)
There is a need of certain number of speech examples to solve real life tasks. A natural speech corpora may suffer from limited phoneme, word or phrase combinations. On the other hand an experimenter can create huge speech corpora using synthetic speech that reflect investigative speech cases that it is similar enough to natural speech. The usage of synthetic and natural speech corpora for speech segmentation algorithm comparison is presented in this paper. The adequateness of synthetic and natural corpora criteria for speech segmentation was proved. The experiments results showed that synthetic signals can be used for speech algorithm research. DOI: http://dx.doi.org/10.5755/j01.eee.18.8.2626